From "territories" to city centers: The ambivalent management of women's safety and gentrification. Issue 1 (April 2018) - Lieber, Marylène
Abstract Recent mobilizations against street harassment, targeting a well-known problem, have recently received a positive response from local governments. Taking Paris as an example, this article will develop an analysis of the various ways in which women's safety in public places has been conceptualized during recent decades and the changes in the way this problem has been defined. It emphasizes the fact that women's safety, which for a long time was both invisible and taken for granted, is now part of a renewed paradigm in public space and is considered to be an element of a city's quality and value where the mobility of "respectable" women becomes a measure of well-being and in turn favors the process of gentrification.